Trend differences over 20 years between two methadone maintenance clinics, one with and one without cannabis legalization. Issue 2 (10th November 2020) - Adelson, Miriam; Smith, Dinita; Peles, Einat
Abstract: Background: Although methadone maintenance treatment (MMT) guidelines are well established, patients' characteristics and outcome change over time may be affected by the legality of cannabis. Objective: To study trend changes between two clinics over 20 years from Las Vegas (LV) and 27 years from Tel Aviv (TA). Methods: Patients' characteristics at admission, including drugs in urine at first and 13th month were obtained from their medical charts. Changes by year of admission and cumulative retention were analyzed. Results: The LV MMT clinic (1724 patients) had a lower one-year retention rate compared to the TA MMT clinic (1014 patients) (46.4% vs. 74.4%, respectively, p  < 0.0005), and a higher rate of opioid stop after one year (75.9% vs. 68.8%, respectively, p  = 0.003). The age at MMT admission and the retention rates decreased in LV and increased in TA. The prevalence of cannabis and benzodiazepine misuse on MMT admission increased in LV with no change recorded in TA. Cocaine on MMT admission decreased in LV and increased in TA, while amphetamine use increased in LV and decreased in TA. Cox models multivariate analyses found cannabis on admission to predict shorter retention in LV (as younger age male and amphetamines), and cannabis after one year in TA (as did cocaine and opiates after one year and BDZ on admission). Conclusion: Although cannabis prevalence increased only in LV where it was legalized, it was associated with poor outcomes in both clinics. Younger age, a known poor outcome predictor, may be related to decreased retention in LV.